2020
DOI: 10.1002/cjce.23898
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study of mixing of cavitating flows in a Venturi tube

Abstract: This work is devoted to a computational investigation of the cavitation and mixing characteristics of two miscible (Schmidt number Sc = 10 3) turbulent water flows with different viscosity ratios in a Venturi tube. The 2D axissymmetric RANS and 3D LES turbulence models are used for the prediction of flow characteristics. The numerical results reveal that the RANS solutions underpredict the rate of vapour production and overestimate the mixing rate of two miscible fluids in comparison to LES simulations for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 32 publications
(48 reference statements)
0
1
0
Order By: Relevance
“…The interior design of the nozzle was similar to a venturi, and many hard and sharp crushing needles were placed on the crushing device. The local pressure in this system fell to the value of the vapor pressure of the liquid medium as the fluid passed through the throat of the micronano bubbles system [21]. This droves the growth of micro-nano cavitation nuclei in the liquid [22].…”
Section: Experimental Apparatusmentioning
confidence: 92%
“…The interior design of the nozzle was similar to a venturi, and many hard and sharp crushing needles were placed on the crushing device. The local pressure in this system fell to the value of the vapor pressure of the liquid medium as the fluid passed through the throat of the micronano bubbles system [21]. This droves the growth of micro-nano cavitation nuclei in the liquid [22].…”
Section: Experimental Apparatusmentioning
confidence: 92%
“…A typical effect sought in the use of Venturi injectors is the generation of vacuum, but at a certain point the depression can produce cavitation, and given the importance of this effect, Shi et al and Bermejo et al [12,13] studied how this cavitation affects and its possible uses. One of these uses is fluid mixing; thus, Shi and Nikrityuk [14,15] studied how this cavitation affects the mixing process.…”
Section: Introductionmentioning
confidence: 99%
“…Tukimin et al (2016) visualized the internal flow field of the Venturi injector and reported that its lowest internal pressure appeared in the throat by Fluent software. When the Venturi injector worked at low inlet pressure, the sensitivity of the injection rate to the pressure difference was highest (Shi et al, 2021). Simultaneously, Shi et al (2019) held that the water–fertilizer mixing area was mainly the diffusion section.…”
Section: Introductionmentioning
confidence: 99%